ANALISIS PENDAPATAN DAN PEMASARAN IKAN CAKALANG DI KELURAHAN LABUAN BAJO KECAMATAN BANAWA KABUPATEN DONGGALA - Hudria, Hudria; Effendy, Effendy (AGROTEKBIS, 2018)
This research aims to know the magnitude of the income of fishermen and the magnitude of the margins of marketing of the sales results of the tuna in Labuan Bajo village, Banawa subdistrict of Donggala Regency. Determination of the respondent of fisherman is done by using a simple random sampling method, where each fisherman has the same possibilities to be used as a sample. The number of respondents that were taken as many as 40 out of a population total of 320 members of the fishermen who try to capture of fishery in Labuan Bajo village, that are 32 fishermen, 4 men of collectors  and 4 men of traders. Result of analysis revenue on research showed that the average receipt obtained by Tuna fish fishermen is Rp. 2,396,283, the average total cost of production of Rp. 590,910. average income of Rp. 1,805,372 per month. Analysis of the marketing of Tuna in Labuan Bajo village is the price received by fishermen on the channel I of 57.69 so efficiency is 15.33% and on channel II the price received the fishermen of 73.07% so the efficiency is 15,39%. The marketing of tuna on channel II is more efficient compared to the channel I, because of the price received by the fishermen on channel II is larger than the channe lI. Keywords: Income, Marketing, Tuna Fishermen, Traders Tuna